Peningkatan pendapatan masyarakat pasca pandemic covid-19 melalui kegiatan pemberdayaan masyarakat untuk mewujudkan desa laboratorium terpadu di Kelurahan Olak Kemang - Teja Kaswari; Heni Suryani; Faradina Zevaya (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2021)
This study aims to (1) Increase community income which fluctuates after the Covid-19 pandemic through the provision of goat livestock assistance, (2) Provide knowledge to the community, especially breeders related to good livestock management, and (3) Provide understanding to the community in Olak Kemang Village in improving the potential quality of agricultural waste as goat feed. The method used is a descriptive and quantitative approach. A descriptive approach was taken to provide an overview of the conditions in Olak Kemang Village supported by field data related to counseling and socialization of livestock rearing management, training on processing agricultural waste as animal feed. The quantitative approach uses an investment analysis of the feasibility of the goat farming business and the socio-economic conditions of the community. The results of this activity show that quantitatively, the calculation of investment analysis and business feasibility can be described that the goat farming business provides a profit of Rp. 30,210,000 so that the average monthly income for each family head is Rp. 359,643. With a partner's level of satisfaction with this activity is more than 80%.